Kajian Kemiringan Menara Syahbandar di Museum Bahari Jakarta dalam Konservasi Arsitektur - R. Siti Rukayah; Athia Maulida Tsania Shofie; Fariz Addo Giovano (Universitas Sebelas Maret Surakarta, 2025)
The Syahbandar tower building is one of the historically valuable buildings in the Old City of Jakarta which was built on top of one of the bastions of the Batavia city fort. The current condition of the Syahbandar Tower is experiencing a slope, so it is necessary to carry out research on the development of the slope that occurs from year to year in order to find a solution for conservation. This research aims to formulate conservation recommendations from the aspect of heritage architecture regarding the current slope of the Syahbandar Tower. The research method is based on visual depictions of field surveys, Google Street View and ancient photos from the beginning of the tower until now. Research findings are based on two-dimensional depictions of architecture. The building slopes towards the neighborhood road by 6.5 degrees. Because of its uniqueness and historical value, architectural conservation efforts are needed, as a form of appreciation for the history of a nation.